Impact of Stakeholder Pressure and Gender Diversity on Corporate Sustainability Disclosure - Luh Gde Pasek Puspa Dewi; Ni Made Dwi Ratnadi; I Gusti Ayu Made Asri Dwija Putri; Made Gede Wirakusuma (Jurnal Ekonomi dan Bisnis Jagaditha)
This study addresses the critical role of sustainability reporting in corporate transparency, yet existing literature shows inconsistent findings regarding stakeholder pressure and board gender diversity’s impact on disclosure practices. This research aims to examine the influence of various stakeholder pressures (creditor, employee, consumer, and shareholder), board gender diversity, and the moderating effect of industry profile on sustainability report disclosure among public companies listed on the Indonesia Stock Exchange from 2018 to 2023. Employing a quantitative approach, data were collected from annual and sustainability reports of 282 companies and analyzed using Moderated Regression Analysis (MRA). The findings reveal that creditor, consumer, and shareholder pressures, along with board gender diversity, positively and significantly influence sustainability disclosure. Conversely, employee pressure shows no significant effect. Industry profile acts as a quasi-moderator, strengthening the positive relationships between creditor, consumer, shareholder pressures, board gender diversity, and sustainability report disclosure. These results suggest that companies operating in high-profile industries, facing greater public scrutiny, are more responsive to external stakeholder demands and board diversity in their sustainability practices. This study contributes to bridging gaps in the literature by clarifying the conditional role of industry context in sustainability reporting and highlights the importance of inclusive governance and stakeholder engagement in promoting transparency. The implications offer valuable insights for regulators and corporate managers seeking to enhance sustainability disclosure quality and accountability.